Clinical profile of hypoglycemia in neonates admitted in neonatal intensive care unit of a tertiary care hospital - Somanathan, Sayooj; Pothapregada, Sriram; Varadhan, Anuradha; Mathew, Ruth Ann (International Journal of Contemporary Pediatrics, 2021)
Background: This study was conducted to study the clinical profile of hypoglycemia in newborn and to determine the prevalence of hypoglycemia among neonates admitted in NICU. Methods: All newborns admitted in NICU were examined and those with hypoglycemia (GMR<45 mg/dl) were included in the study and observed. In neonates with risk factors blood sugar was screened at 2, 6, 12, 24, 48 and 72 hours of life or whenever symptoms suggestive of hypoglycemia developed in any neonates and for critically sick neonates blood sugar was screened in every 6 hour in active phase of illness. Any neonates with blood glucose level less than 45 mg/dl were analysed for maternal risk factors, neonatal risk factors and course in the NICU. Results: The prevalence of neonatal hypoglycemia was 14.9% among NICU admissions. The maternal risk factors were GDM, PIH, and PROM. The neonatal risk factors were prematurity, SGA, LGA and comorbid conditions which include perinatal asphyxia, sepsis, polycythemia, shock. The common symptoms were poor feeding, lethargy, jitteriness, convulsions, irritability, hypotonia and cyanosis. Majority of the neonates required only oral feeds for correction of hypoglycemia. Conclusions: Blood glucose screening in neonates with this risk factor is mandatory as many of the neonates were asymptomatic. The importance of early initiation of breast feeding to prevent hypoglycemia should be emphasized.